Dietary Vitamin C Intake Is Associated With Improved Liver Function and Glucose Metabolism in Chinese Adults - Luo, Xiaoqin; Zhang, Wanyu; He, Zhangya; Yang, Hexiang; Gao, Jiayi; Wu, Pei; Ma, Zheng Feei (Frontiers in Nutrition, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent chronic liver diseases worldwide. Dietary vitamin C intake may play an important role in reducing the risk of NAFLD. The aim of the study was to assess the relationship between dietary vitamin C intake and diagnostic biomarkers of NAFLD. Methods: The data from the 2009 China Health and Nutrition Survey (CHNS), nine provinces across four diverse regions (Northeast, East Coast, Central and West) were included in the study. Dietary vitamin C intake of participants was calculated based on 3-day 24-hour diet questionnaires at the individual level. The associations of dietary vitamin C intake and the biochemical indicators of liver function and glucose/lipid metabolism were determined. Results: A total of 8307 participants were included in the final analysis. The mean dietary vitamin C intake for the overall, male and female subjects was 79.8 ± 58.6 mg/day, 81.6 ± 55.3 mg/day, and 78.2 ± 61.2 mg/day, respectively. The prevalence of inadequate dietary vitamin C intake for the overall, male and female subjects was 24.4%, 26.5%, and 22.6%, respectively. Intake of vitamin C was associated with both lower concentrations of plasma ferritin and haemoglobin A1c (HbA1C). Higher dietary vitamin C intake was associated with higher albumin, even further adjusted for BMI, residence and smoking status. No any improvement of lipid metabolism was found. Conclusions: Our study demonstrated that higher dietary vitamin C intake is benefit for improving glucose metabolism, and liver function in which reducing ferritin, a biomarker of iron accumulation, may be involved.